Técnicas activas para el aprendizaje de las cuatro operaciones básicas de Matemática en los cuartos años de Educación General Básica de la Unidad Educativa San José de Guaytacama. - Proaño Hidalgo, Bethy Estela (2020)
The research carried out aims to solve the problem, how to improve the learning of the four basic operations of Mathematics with the application of active techniques in the fourth years of Basic General Education of the San José de Guaytacama Educational Unit, for which it was proposed as a general objective, develop a didactic guide to perfect the learning of addition, subtraction, multiplication and division, through the application of entertaining techniques such as games; To achieve the objective, the mixed approach identified with quantitative and qualitative research, inductive, deductive, analytical, synthetic methods, modeling, empirical methods such as observation, the survey technique and the questionnaire instrument will be used; Among the statistical methods, descriptive statistics were used, obtaining as a result a didactic guide with active techniques (games) for learning the four basic operations of Mathematics, which was validated through the evaluation of experts, the criteria of users, as well as socialization workshops, results support the viability, the reliability for its implementation based on the solution of the research problem.